Behavioral Alterations of Ethanol on Lithium Treated Methylphenidate Induced Mania Like Phenotype and Corticosterone Induced Depression Like Phenotype in Swiss Albino Mice - Balamurugan, Elumalai (International Journal of Pharmaceutical & Biological Archive, 2014)
Behavioral Alterations of Ethanol on Lithium Treated ethylphenidate Induced Mania Like Phenotype and Corticosterone Induced Depression Like Phenotype in Swiss Albino Mice